2013
DOI: 10.1590/s1806-37132013000300004
|View full text |Cite
|
Sign up to set email alerts
|

Does thromboprophylaxis prevent venous thromboembolism after major orthopedic surgery?

Abstract: OBJECTIVE: Pulmonary embolism (PE) is an important complication of major orthopedic surgery. The aim of this study was to evaluate the incidence of venous thromboembolism (VTE) and factors influencing the development of VTE in patients undergoing major orthopedic surgery in a university hospital. METHODS: Patients who underwent major orthopedic surgery (hip arthroplasty, knee arthroplasty, or femur fracture repair) between February of 2006 and June of 2012 were retrospectively included in the study. The incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 16 publications
1
34
0
Order By: Relevance
“…9 Accordingly, the benefits of prophylaxis in older adult orthopedic surgical populations have also been consistently noted. 30 Our results suggest that this effect of age on the risk of VTE also applies to the pediatric population, a finding which is also consistent with several previous reports. 3, 5, 6, 10 Interestingly, the 2012 recommendations from the American College of Chest Physicians on the prevention of VTE in orthopedic surgery patients state that even though increasing age is associated with VTE, in general, surgery-specific risks outweigh patient specific factors.…”
Section: Discussionsupporting
confidence: 93%
“…9 Accordingly, the benefits of prophylaxis in older adult orthopedic surgical populations have also been consistently noted. 30 Our results suggest that this effect of age on the risk of VTE also applies to the pediatric population, a finding which is also consistent with several previous reports. 3, 5, 6, 10 Interestingly, the 2012 recommendations from the American College of Chest Physicians on the prevention of VTE in orthopedic surgery patients state that even though increasing age is associated with VTE, in general, surgery-specific risks outweigh patient specific factors.…”
Section: Discussionsupporting
confidence: 93%
“…After screening title/abstract and full‐text information, 728 were excluded because of duplicated publications, and 1610 were excluded because the data they provided was not available or unrelated to our topic. Finally, 23 articles that met the inclusion criteria were included in this meta‐analysis . The flow chart of the search strategy is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…All studies reported data on the incidence of VTE . The pooled estimates, using a random‐effect model, indicated that the incidence of VTE in patients who underwent surgery for fractures below the hip was 21% (95%CI: 17%, 24%; P = 0·000) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…As a kind of mild thrombosis, thrombosis of calf muscular veins requires proper treatment during each section of the perioperative period. 4,5 As seen in our case, calf muscular venous thrombosis is not constant and might ascend to involve the thigh, even the common iliac vein with the increased duration of bed rest and performance of surgery. This may deteriorate the patient condition and cause life-threatening complications.…”
Section: Discussionmentioning
confidence: 46%
“…Besides, the coagulation function was regularly checked and the dose of warfarin was adjusted according to the international normalized ratio. [3][4][5] On the 11 th day after surgery, the edema of the left lower limb was alleviated, nevertheless, color Doppler ultrasonography indicated that thrombosis has ascended to the left common iliac vein and external iliac vein. Considering the elevation of the thrombosis level, a filter was placed in the inferior vena cava the same day (Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 99%